2023
DOI: 10.1002/msc.1834
|View full text |Cite
|
Sign up to set email alerts
|

Patient access to first contact practitioner physiotherapists in the UK: A national survey

Kirsten Lamb,
Christine Comer,
Nicola Walsh
et al.

Abstract: BackgroundFirst Contact Practice Physiotherapists (FCPPs) offer expert care for patients with musculoskeletal (MSK) conditions in Primary Care, usually within GP practices. This is a rapidly expanding area of practice endorsed by NHS England, the Chartered Society of Physiotherapy (CSP) and the British Medical Association (BMA). Efficient and appropriate access is important for optimising FCPP practice, but there is little published information about how patients currently access FCPP appointments.ObjectiveTo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…It provides new evidence about patient reported facilitators and barriers to access, as well as confirming key access routes, and the challenges of low awareness of the FCPP role. A previous study found that there are a variety of access routes into FCPP appointments, with the most common way being booking via Reception (Lamb et al., 2023a); another study noted that many patients have seen or spoken to a GP about their MSK condition before receiving an FCPP appointment (Lamb et al., 2023b). In this current study, five of the 13 participants had only seen the FCPP after first having a GP appointment, and one of the patients' surgeries required a GP appointment prior to FCPP input.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It provides new evidence about patient reported facilitators and barriers to access, as well as confirming key access routes, and the challenges of low awareness of the FCPP role. A previous study found that there are a variety of access routes into FCPP appointments, with the most common way being booking via Reception (Lamb et al., 2023a); another study noted that many patients have seen or spoken to a GP about their MSK condition before receiving an FCPP appointment (Lamb et al., 2023b). In this current study, five of the 13 participants had only seen the FCPP after first having a GP appointment, and one of the patients' surgeries required a GP appointment prior to FCPP input.…”
Section: Discussionmentioning
confidence: 99%
“…The interview topic guide was informed by the aim of the research as well as by the results of the scoping review and survey of access methods previously performed by the authors (Lamb et al, 2023a(Lamb et al, , 2023b. It was developed by discussion among the authors, and there were no patients involved due to time constraints.…”
Section: Interview Topic Guide Developmentmentioning
confidence: 99%
See 2 more Smart Citations